A novel auxiliary fixation technique of meshes in intraperitoneal onlay mesh procedures for incisional hernia repair - Zhang, Kunjie; Lin, Jiayu; Qin, Lianjin; Li, Leqi; Xia, Changjun; Li, Jianfang (Frontiers in Surgery, 2023)
Mesh fixation is an important step in incisional hernia repair. Weak fixation possibly results in postoperative pain, and even hernia recurrence. We innovated an auxiliary fixation approach, the magnet attraction technique (MAT), to achieve better mesh fixation. The purpose of this study was to evaluate the effect of MAT in intraperitoneal onlay mesh (IPOM) procedures for incisional hernia repair. Historical patient records were analyzed according to the clinical data of 16 patients with incisional hernias. Among them, 5 patients have undergone IPOM repair procedures in combination with MAT to assist in mesh fixation. As a control, 11 patients treated with IPOM and mesh fixation via conventional suspension were included. The clinical data collected include patients’ basic characteristics, intraoperative and postoperative conditions, and follow-up results in both groups. Compared with patients in the control group, patients in the MAT group were found to suffer from a larger hernia ring diameter and longer surgical duration, but shorter hospitalization length on average. And most importantly, no complication has been reported in the MAT group. Therefore, MAT in IPOM operation was regarded as a feasible and safe technique for patients suffering from incisional hernias.